On Codes Over R and its Bounds of Some kind of Block Repetition Codes in R - P Chella Pandian (InPrime: Indonesian Journal of Pure and Applied Mathematics, 2022)
This correspondence determines the lower and upper bounds of the covering radius in some kind of block repetition codes over the ﬁnite ring R=Z_2 Z_*, where Z_*=Z_2+vZ_2+v^2 Z_2, v^3=v. For covering radii of binary and octonary block repetition code over R is also discussed. This leads to the convenient formulation of code and arrives at the bounds. Keywords: block repetition codes; covering radius; different weight; finite ring. Abstrak Korespondensi ini menentukan batas bawah dan batas atas dari jari-jari penutup suatu kode blok perulangan pada gelanggang hingga R=Z_2 Z_*, dengan Z_*=Z_2+vZ_2+v^2 Z_2, v^3=v. Dibahas juga jari-jari kode blok perulangan biner dan oktonari atas R. Diperoleh rumus untuk kode dan batasnya. Kata Kunci: kode blok perulangan; penutup jari-jari; berat yang berbeda; gelanggang hingga. 2020MSC: 11T71, 94B05, 11H71.